On the need for a comprehensive legal regulation to prevent food waste - Sokołowski, Łukasz Mikołaj (Przegląd Prawa Rolnego, 2019)
Combating food waste is one of the greatest contemporary challenges for agriculture, the CAP and the legislator. The aim of the considerations is to answer the question whether and to what extent the legislation, both EU and national, provides for instruments to counteract this phenomenon. There are no comprehensive legal solutions that would allow effective prevention of food waste. However, at the EU level there is an observable process of setting up foundations for future policies and legal frameworks for actions aimed at limiting and combating this phenomenon. The mere fact that the problem has been noted by the legislator and the previous, albeit partial, normative regulation on combating food waste is a positive development. The measures already undertaken may constitute the first steps on the way to implementing comprehensive solutions that will, at the same time, be a manifestation of the legislator’s efforts to ensure food sovereignty based on a closed-loop economy.